Strategic control of cattle co-parasitized by tick, fly and gastrointestinal nematodes: Is it better to use ecto + endoparasiticide or just endectocide formulations? - Gomes, Lucas Vinicius Costa [UNESP]; Teixeira, Weslen Fabricio Pires [UNESP]; Maciel, Willian Giquelin [UNESP]; Felippelli, Gustavo [UNESP]; Buzzulini, Carolina [UNESP]; Soares, Vando Edésio [UNESP]; de Melo, Daniel Pacheco [UNESP]; Cruz, Breno Cayero [UNESP]; Rodrigues, Daniel de Castro; Ferreira, Lorena Lopes; Monteiro, Caio Marcio de Oliveira; Lopes, Welber Daniel Zanetti; et al. (Elsevier, 2022)
Ticks, flies, and gastrointestinal helminths (GINs) significantly affect cattle productivity; thus, ectoparasiticide, endoparasiticide, and endectocide drugs have commonly been used for their control. The study aimed to compare the technical (parasites counts), productive, and financial effects of a treatment protocol comprising ecto- + endoparasiticides formulations (T01: fluazuron 2.5 mg/kg + fipronil 1.25 mg/kg and fenbendazole 5 mg/kg; n = 15) to a treatment with one formulation of endectocide (T02: ivermectin 450 μg/kg + abamectin 250 μg/kg; n = 15) over 308 days under field conditions in crossbred cattle co-parasitized by Rhipicephalus microplus, Haematobia irritans, and GINs. Bovine weight gain and return on investment (ROI) were also evaluated. Bovines from T01 received four treatments against the cattle tick and two against two GINs. For T02, four treatments were performed. Animals from T01 gained 15.4 kg more than T02 and provided a comparative ROI of 15.8. In cattle co-parasitized with R. microplus, H. irritans, and GINs, the treatment protocol used in this study with ecto- + endoparasiticidal action formulations showed better technical results regarding parasite counts and productive and financial data than the strategic treatment protocol using only an endectocide formulation.
Keywords: Gastro-intestinal nematodes; Haematobia irritans; Return on investment; Rhipicephalus microplus; Strategic control